2005
DOI: 10.1103/physrevb.72.140407
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed magnetization inLa0.7Ca0.3MnO3YBa2Cu3O7

Abstract: We studied the magnetic properties of La 0.7 Ca 0.3 MnO 3 / YBa 2 Cu 3 O 7−δ superlattices. Magnetometry showed that with increasing YBa 2 Cu 3 O 7−δ layer thickness the saturation magnetization per La 0.7 Ca 0.3 MnO 3 layer decreases. From polarized neutron reflectometry we determined that this magnetization reduction is due to an inhomogenous magnetization depth profile arising from the suppression of magnetization near the La 0.7 Ca 0.3 MnO 3 / YBa 2 Cu 3 O 7−δ interface.Electron energy loss spectroscopy in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
65
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 24 publications
6
65
1
Order By: Relevance
“…before this problem with the STO substrates had been fully appreciated, additional experiments of YBCO/LCMO SLs on STO substrates were reported that supported either the dead layer model or the inverse proximity effect model. Hoffmann et al reported an enhancement in the Mn 3d occupation next to the interface and concluded that their PNR data support the dead layer model 27 . On the other hand, Chakhalian et al reported x-ray magnetic circular dichroism (XMCD) data which established the presence of a ferromagnetic Cu moment and thus were interpreted in terms of the "inverse proximity effect model" 28 31 .…”
mentioning
confidence: 63%
“…before this problem with the STO substrates had been fully appreciated, additional experiments of YBCO/LCMO SLs on STO substrates were reported that supported either the dead layer model or the inverse proximity effect model. Hoffmann et al reported an enhancement in the Mn 3d occupation next to the interface and concluded that their PNR data support the dead layer model 27 . On the other hand, Chakhalian et al reported x-ray magnetic circular dichroism (XMCD) data which established the presence of a ferromagnetic Cu moment and thus were interpreted in terms of the "inverse proximity effect model" 28 31 .…”
mentioning
confidence: 63%
“…While interesting macroscopic properties such as exchange bias [7] and giant magnetoresistance [10] were observed in some of these structures, the presence of microscopic proximity effects is still under intense investigation [3]. Some experiments have yielded evidence of a strongly suppressed ferromagnetic magnetization on the LCMO side of the interface [5,12], whereas others conclude that copper spins on the YBCO side of the interface are polarized by exchange interactions across the interface, partially compensating the ferromagnetic magnetization of LCMO [13]. Interplay between ferromagnetic and superconducting order parameters [1] is unlikely to be responsible for either of these effects, because the microscopic magnetic properties are not noticeably affected by the superconducting transition [15].…”
mentioning
confidence: 99%
“…Interplay between ferromagnetic and superconducting order parameters [1] is unlikely to be responsible for either of these effects, because the microscopic magnetic properties are not noticeably affected by the superconducting transition [15]. Rather, charge transfer across the interface [12,14] and an orbital reconstruction due to the formation of a covalent bond across the interface [14] have been invoked as explanations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced Curie temperature and enhanced coercivity of the top layer may be related to changes of the electronic structure at the interface caused by strain, to modified chemical bonding, or even to charge transfer as recently reported for cuprate/manganite heterostructures. 14 Interface effects are expected to be more pronounced in the thinner top layer than in the bottom one. The difference in coercive fields ensures antiparallel alignment of the magnetization of bottom and top electrodes over a wide field interval.…”
mentioning
confidence: 99%